2005
DOI: 10.1007/s10519-004-0857-4
|View full text |Cite
|
Sign up to set email alerts
|

Genetic and Developmental Influences on Infant Mouse Ultrasonic Calling. III. Patterns of Inheritance in the Calls of Mice 3?9 Days of Age

Abstract: Infant mice produce ultrasonic calls that may elicit retrieval by adult mice. Age-related differences and genetic effects, such as additivity and directional dominance, have been found for most call characteristics at 3 days of age. Significant maternal effects have been reported for calling rate. However, little is known about how the influence of these genetic effects changes with age. This study explored developmental-genetic patterns of inheritance of seven ultrasonic call characteristics at ages 3-9 days,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
39
1

Year Published

2005
2005
2016
2016

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 46 publications
(50 citation statements)
references
References 26 publications
8
39
1
Order By: Relevance
“…This is in accordance with a bulk of observations of strain differences in the emission of ultrasonic vocalizations in mice (Bell et al 1972;Cohen-Salmon et al 1985;Hahn et al 1987Hahn et al , 1997Hahn et al , 1998Hahn and Schanz 2002;Hennessy et al 1980;Robinson and D'Udine 1982;Roubertoux et al 1996;Sales and Smith 1978;Thornton et al 2005), and adds to other differences between B6JOla and B6N.…”
Section: Within-strain Embryo-transfer: Comparison Between B6jola Andsupporting
confidence: 91%
See 3 more Smart Citations
“…This is in accordance with a bulk of observations of strain differences in the emission of ultrasonic vocalizations in mice (Bell et al 1972;Cohen-Salmon et al 1985;Hahn et al 1987Hahn et al , 1997Hahn et al , 1998Hahn and Schanz 2002;Hennessy et al 1980;Robinson and D'Udine 1982;Roubertoux et al 1996;Sales and Smith 1978;Thornton et al 2005), and adds to other differences between B6JOla and B6N.…”
Section: Within-strain Embryo-transfer: Comparison Between B6jola Andsupporting
confidence: 91%
“…Also, genetic analyses using reciprocal hybrids (Hahn et al 1987(Hahn et al , 1997(Hahn et al , 1998Hahn and Schanz 2002;Roubertoux et al 1996;Thornton et al 2005) revealed an influence of the genetic background on ultrasonic call emission; a finding, which is supported by studies on knockout mice. For instance, it was shown that several genes are involved in the production of ultrasonic vocalizations, especially Foxp2 (Shu et al 2005).…”
Section: Within-strain Embryo-transfer: Comparison Between B6jola Andmentioning
confidence: 64%
See 2 more Smart Citations
“…3 bottom). This pattern is also seen in M. m. domesticus [2,11]. The mean peak frequency was about 75 kHz.…”
Section: Analysis Of Vocalizations Emitted By Adult Kor1 Malesupporting
confidence: 64%